2021
DOI: 10.1111/ijcp.15004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hyoid bone morphology between obstructive sleep apnea patients and healthy individuals

Abstract: Objective We aimed to find morphological properties of the hyoid bone, which are predominant among the patients diagnosed with obstructive sleep apnoea (OSA), and compare them with healthy individuals. Methods A total of 67 cone‐beam computed tomography (CBCT) image sequences of patients (44 males, 23 females) diagnosed with OSA and a total of 70 multislice computed tomography (MSCT) data of non‐OSA patients (45 males, 25 females) were selected in this study. DICOM images were imported into InVivo 5.1.2 (Anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…So, its position plays an important role in the pathophysiology of pharyngeal airway obstruction through muscle force vectors which could be associated with increased upper airway collapsibility [ 17 ]. A recent study has suggested volumetric differences of the hyoid bone as a potential biological marker for OSA [ 18 ]. The hyoid bone is relatively easy to identify on radiographs compared to other landmarks reducing the influence of an examiner’s aptitude [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…So, its position plays an important role in the pathophysiology of pharyngeal airway obstruction through muscle force vectors which could be associated with increased upper airway collapsibility [ 17 ]. A recent study has suggested volumetric differences of the hyoid bone as a potential biological marker for OSA [ 18 ]. The hyoid bone is relatively easy to identify on radiographs compared to other landmarks reducing the influence of an examiner’s aptitude [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study involving this analysis, Salles et al 31 (2005) assessed individuals with OSA and showed that the hyoid bone is located at the level of the C4-C6 cervical vertebrae, which increases the HMP to about 27.8 mm, while in healthy individuals the average distance is of 12 mm. Kurbanova et al 33 (2021) correlated cephalometric facial pattern measurements with the position of the hyoid bone using computed tomography (CT) in adults diagnosed with OSA, and they suggested that the hyoid bone could be a potential biological marker for OSA. In line with the present study, Ryu et al 26 (2015) and Soares et al 32 (2020) found a direct correlation between inferiorization of the hyoid bone and the AHI, using the HMP.…”
Section: Discussionmentioning
confidence: 99%
“…The hyoid bone with its body and greater and lesser horns, is often an overlooked small anatomical structure, although it gives attachment to several muscles and ligaments of the neck and plays a vital role in the craniomandibular functions (23). Hyoid bone position has been frequently studied in relation to oropharyngeal space dimensions (24), facial growth patterns (25), craniofacial anomalies (20), obstructive sleep apnea syndrome (26), myofascial pain (27), atypical deglutition (28), and temporomandibular joint disc displacement (29). The hyoid position in relation to carotid artery diseases as its proximity to the carotid bifurcation level is a rarely studied phenomenon, although there are several case reports describing CVAs due to unilateral compression of the hyoid bone through its greater horn (9,11,12,23,30).…”
Section: Discussionmentioning
confidence: 99%